Die semantische Datenmodellierung im Corpus der barocken Deckenmalerei in Deutschland - Albers, Laura (Digitale Raumdarstellung: Barocke Deckenmalerei und Virtual Reality, 2020)
Keywords: CIDOC CRM; digitale Erfassung; digitales Projekt; implizites Wissen; Semantic Web; semantische Datenmodellierung

Representing place in space and time - methodological aspects in modelling the provenance of cultural heritage knowledge - Albers, Laura; Görz, Günther (Provenance of Knowledge. Proceedings, 2018)
Event-based modelling provides obvious advantages for the modelling of provenance information. In particular, the concept of “place” plays an important role; we compare different definitions and their background. Next, we look at the use of “place” in gazetteers, which are important resources for cultural heritage information, and the relation between place names and their temporal dimension. If we use CIDOC CRM for provenance modelling, the question comes up to what extent the concept of “place” as understood in CRM and its extension CRMgeo provide means to enable interoperability. Originating from a consideration of modelling alternatives in CRM ver. 5 (without CRMgeo), we point out the advantages provided by the integration of CRMgeo into CRM ver. 6. Nevertheless, there are still open questions, and we have to find pragmatic solutions in practical applications. Finally, we present the Bavarian Academy project “Corpus of Baroque Ceiling Paintings in Germany” as an example.<br
UnivIS-Import:2019-08-15:Pub.2018.tech.IMMD.lehstu.agdigi.repres

Semantic Data-Modeling and Long-Term Interpretability of Cultural Heritage Data - Three Case Studies - Wagner, Sarah; Albers, Laura; Große, Peggy (Digital Cultural Heritage, 2019)
Research institutions and museums are increasingly initiating projects where large amounts of metadata are collected that describe both the content and the context of the collected data. The use of semantic methods enables their connection. In addition, these data must remain interpretable by man and machine even after the end of funded research projects. Therefore, the data-model used has to enable a mapping of the content and context of the respective research project as well as to develop the digital resources on a sustainable basis. In the following, three different projects with diverse topics are presented, in which domain knowledge is modeled on the basis of an ontology, in this case the CIDOC Conceptual Reference Model (CRM).<br

Semantische Datenmodellierung mit CIDOC CRM – Drei Fallbeispiele - Wagner, Sarah; Albers, Laura; Große, Peggy (INFORMATIK 2017 | DIGITALE KULTUREN, 2017)